Pengaruh Brand Image, Brand Awareness, Dan Product Quality Terhadap Keputusan Pembelian Hp Iphone (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Najih, M. Ulul Ikhwanin; Wahono, Budi; Rizal, Mohammad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstrak This research is motivated by the emergence of the very rapid phenomenon of mobile phone domination in Indonesia. Apart from that, the level of intense competition in various cellphone product categories based on technological advances has led to the emergence of several quite interesting phenomena which encourage consumers to buy iPhones which are currently in demand on the market according to the product they want. This research uses the gap phenomenon, the problem studied in this research is whether brand image, brand awareness and product quality influence purchasing decisions both partially and simultaneously. The aim of this research is to determine the influence of brand image, brand awareness and product quality on purchasing decisions among students at the Faculty of Economics and Business, Islamic University of Malang. The population in this study was a sample size of 975 with a sample of 91 respondents using snowball sampling. The data used is multiple regression analysis. The research results showed that brand image, brand awareness and product quality simultaneously influence purchasing decisions. The conclusion from this research is that brand image and brand awareness partially influence purchasing decisions. Meanwhile, product quality has no partial effect on purchasing decisions. Keyword : Making Decision, Brand Image, Brand Awareness, Product Quality